Application of Domestic High-voltage Inverter in the Driving System of Grinding Roll for Mines - PAN Yan; HE Bojun; WANG Shiping (Kongzhi Yu Xinxi Jishu)
Based on the analysis of technological process of crushing and high pressure grinding, the requirements of variablefrequency speed-regulation of high pressure grinding system were researched. According to the requirement of speed regulation, the speed regulating strategy, cooperative control strategy and load power fluctuation regulating strategy of high voltage inverter were analyzed. Practical operation waveforms of the high pressure grinding system verified that the high voltage inverter had favourable dynamic response and stable speed following of acceleration and deceleration, and the correctness and validity of the host and slave cooperative control strategy were also verified by the practical operation waveforms of the system.